Cicatrização após fotobiomodulação com led em lesões por pressão: estudo clínico controlado randomizado - Ferreira, Rita de Cássia (2017)
The high incidence of pressure injuries is considered a serious public health problem and a negative indicator in the quality of nursing care. The main objective of this study was to evaluate the healing after photobiomodulation with red LED in pressure lesions stages 3 and 4 of patients hospitalized in a public hospital in the State of São Paulo. The study was clinical, randomized and controlled divided into two groups, CG (conventional group, n = 8) and GLED (LED group, n = 7). GC procedures were performed once daily with physiological solution and hydrogel with sodium alginate and cellulose membrane as the secondary coating. While in GLED dressings were done twice a day, cleaning with physiological solution and red LED (λ=664±20[nm], P=15.0mW, I=4.8mW/cm2, H=2.9J/cm2, E=9.0J, t=10min). The evaluation of healing was performed using the PUSH and Fugulin scales, measuring the area, temperature and pH of the lesion. The Origin Pro 2017 software was used to perform the statistical analysis with α= 0.05. In GLED, the variation of the PUSH instrument score was -14.3  14.2 [%], while in the GC it was 0.0  6.7 [%] (p = 8.30094x10-9). About variation of the Fugulin instrument score, in the GLED it was 0.0  8.8 [%], while in the GC it was 0.0  5.8 [%] (p=0.24748). In GLED, area variation was -2.4  28.4 [%], while in GC it was -1.3  17.2 [%] (p=0.09077). The variation in lesion temperature in GLED was - 0.9  5.8 [%], while in GC it was -4.6  9.8 [%] (p=1.6445x10-4). About pH of the lesion, in GLED the variation was 6.1  6.7 [%], whereas in the GC it was 0.0  12.1 [%] (p=0.23011). The data evaluated showed that the evolution of the PUSH scale was favorable to the cicatrization process in the LED group. The scores were high according to the FUGULIN scale, showing a great degree of severity of the patients. LED photobiomodulation was as effective as the conventional treatment proposed in the treatment of pressure lesions, with the advantage of the practicality and quality of its healing process. However, further studies with larger samples are required for this therapy to be included as standard procedure in the hospital setting.